Interventional radiology procedures in biopsy and drainage - Gervais, Debra; Sabharwal, Tarun; SpringerLink (Online service). (New York Springer, 2011)
The Techniques in Interventional Radiology series of handbooks describes in detail the various interventional radiology procedures and therapies that are in current practice. The series comprises four titles, which in turn cover procedures in angioplasty and stenting, transcatheter embolization and therapy, biopsy and drainage and ablation. Forthcoming are volumes on pediatric interventional radiology and neurointerventional radiology. Each book is laid out in bullet point format, so that the desired information can be located quickly and easily. Interventional radiologists at all stages, from trainees through to specialists, will find this book a valuable asset for their practice. Interventional Radiology Procedures in Biopsy and Drainage presents the full array of operations using these techniques. The book is split into two sections ? one dedicated to biopsy procedures and the other to drainage procedures. Dr. Debra Gervais is Director of Pediatric Imaging and Associate Director of Abdominal Imaging and Intervention at Massachusetts General Hospital, Boston, Massachusetts, USA. Dr. Tarun Sabharwal is a Consultant Interventional Radiologist at Guy?s and St Thomas? Hospital, London, UK.
General Principles of Biopsy and Drainage -- Liver Biopsy -- Chest Biopsy -- Mediastinal Biopsy -- Bone Biopsy -- Adrenal Biopsy -- Renal Biopsy -- Pancreatic Biopsy -- Lymph Node Biopsy -- Splenic Biopsy -- Thyroid Biopsy -- Prostate Biopsy -- Drainage of Abdominal Fluid Collections -- Drainage of Pelvic Fluid Collections -- Drainage of Intrathoracic Fluid Collections -- Drainage of Liver Abscess and Fluid Collections -- Drainage of Pancreatic Abscess and Fluid Collections -- Percutaneous Biliary Drainage and Stenting -- Percutaneous Cholecystostomy and Cholecystolithotomy -- Percutaneous Nephrostomy and Antegrade Ureteric Stenting -- Fluoroscopy-Guided Percutaneous Renal Access for Treatment of Stone Disease -- Percutaneous Gastrostomy and Gastrojejunostomy.
Electronic reproduction.
Keywords: Needle biopsy; Drainage, Surgical; Radiology; Electronic books